2017
DOI: 10.5312/wjo.v8.i7.574
|View full text |Cite
|
Sign up to set email alerts
|

Return to sport following tibial plateau fractures: A systematic review

Abstract: AIMTo systemically review all studies reporting return to sport following tibial plateau fracture, in order to provide information on return rates and times to sport, and to assess variations in sporting outcome for different treatment methods.METHODSA systematic search of CINAHAL, Cochrane, EMBASE, Google Scholar, MEDLINE, PEDro, Scopus, SPORTDiscus and Web of Science was performed in January 2017 using the keywords “tibial”, “plateau”, “fractures”, “knee”, “athletes”, “sports”, “non-operative”, “conservative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
0
18
0
4
Order By: Relevance
“… 47 Return to sport is typically at 7–12 months after operative fixation of a tibial plateau fracture. 48 No data have been published on return to sport for nonoperatively treated tibial plateau fractures, though standard guidelines of radiographic union, full motion, normal strength, and proprioceptive control will direct sport resumption.…”
Section: Lower Extremitymentioning
confidence: 99%
“… 47 Return to sport is typically at 7–12 months after operative fixation of a tibial plateau fracture. 48 No data have been published on return to sport for nonoperatively treated tibial plateau fractures, though standard guidelines of radiographic union, full motion, normal strength, and proprioceptive control will direct sport resumption.…”
Section: Lower Extremitymentioning
confidence: 99%
“…In this review, the methodological quality of studies was lower than that of previous similar systematic reviews looking at return to sports following various fracture types, with a mean CMS of 59.5[16-20]. Thus, despite the inclusion of two randomised controlled trials in this study[9,10], this demonstrates a need for further high-quality research in this area including level one studies.…”
Section: Discussionmentioning
confidence: 70%
“…The modified Coleman methodology score (CMS) was employed to determine the quality of the included studies[14]: This has been used in a number of similar reviews[15-20]. The studies were scored by all three authors: the inter-observer reliability of the scoring process was 0.92 (95% confidence interval (CI): 0.90–0.94).…”
Section: Methodsmentioning
confidence: 99%
“…Fractures of the tibia plateau had a significant impact on the patients’ lives, decreasing their quality of life and reducing the involvement with sporting activities. Robertson et al 38 in their review study report that patients sustaining a tibia plateau fracture have lower return to sport rates compared to other injury types. Kraus et al 39 found significant decline of these patients’ sporting activity levels 2 years post treatment.…”
Section: Discussionmentioning
confidence: 99%